Focus on photography [videorecording] - Stoddard, Fran.; The International Center of Photography (Chicago EBEC [producer], 1986)
A guide through the technical and artistic evolution of photography as a means of expression and exploration. Discusses the influence photographs have in our everyday experiences. Demonstrates the workings of the camera, aid the processes of film development, and presents a historical perspective of the photograph itself.
VHS.
Narration, Eric Michaels, Jeff Ryback, Fran Stoddard.
Keywords: Photography